An AN ANALYSIS OF STUDENTS’ MOTIVATION USING GOOGLE CLASSROOM IN LEARNING READING COMPREHENSION (A Study at the First Grade Students of Institut Pendidikan Tapanuli Selatan in 2020/2021 Academic Year) - Nina Nurbaidah (Jurnal Education and Development, 2021)
This research aims to explain the students’ motivation in learning reading comprehension by using google classroom media. This research is a qualitative research method. The writer choose Institut Pendidikan Tapanuli Selatan as the location of the research. The informant of this research are all of the students at the first grade of English Department Institut Pendidikan Tapanuli Selatan. The researcher used questionaire in analyzing students’ motivation in using google classroom. Methodology of the research was a qualitative research. The result from the questionnaire showed that most of the students agreed and strongly agreed that Google Classroom was implemented in the students’ classroom. The result from this article also showed that the students’ motivation in learning online reading comprehension using Google Classroom got positive responses and they learned with high motivation. Keywords: motivation, reading comprehension, and google classroom.